The Gendered Spaces of Globalization - Salonga, Aileen O. (Review of Women's Studies; Vol 21 No 1 (2011): Review of Women's Studies Volume XXI, Number 1 (January-June 2011))
Using a discourse analysis of texts produced and consumed within globalization, this paper examines globalization as a gendered territory in which feminine and masculine spaces are carved out and invested with particular values. Specifically, the paper shows how these spaces are gendered through the use of stereotypical representations of femininity and masculinity. In the end, the paper argues that a discourse analytical framework is critical in revealing how the gendering process works, shedding light on the material construction of gender within globalization.